2015
DOI: 10.1177/2325967115611660
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes and Predictors of Success After Revision Anterior Cruciate Ligament Reconstruction

Abstract: Background:Patient outcomes and predictors of success after revision anterior cruciate ligament (ACL) reconstruction are currently limited in the literature. Existing studies either have a small study size or are difficult to interpret because of the multiple surgeons involved in the care of the study sample.Purpose:To determine patient outcomes and predictors of success or failure after a single-stage revision ACL reconstruction by a single fellowship-trained senior surgeon at a single institution.Study Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
5
10
2
1
Order By: Relevance
“…In the present series, patients who remained symptomatic for more than 1 year following the failure of the graft had inferior outcome scores (IKDC) than those who presented early following failure of the graft. Our experience is different from that of Johnson et al who found no significant correlation between the outcome scores and the time interval between failure and revision 26…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present series, patients who remained symptomatic for more than 1 year following the failure of the graft had inferior outcome scores (IKDC) than those who presented early following failure of the graft. Our experience is different from that of Johnson et al who found no significant correlation between the outcome scores and the time interval between failure and revision 26…”
Section: Discussioncontrasting
confidence: 99%
“…There was no significant difference in outcomes between revisions using B-T-B and hamstring grafts in our series. This is similar to the experience of other authors in earlier reports 26272829…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Abb. 4; [18]). Die Ergebnisse nach Revisionskreuzbandchirurgie sind erwartungsgemäß schlechter als nach Erstoperation [19,20].…”
Section: "Return To Play"unclassified
“…Although ACLR is a common procedure, less than satisfactory outcomes have been reported to occur in up to 25% of patients. 4 The reasons for clinical failure after ACLR are numerous but can be broadly separated into 3 categories: technical, biological, and mechanical failures. Revision ACLR can be performed in 1 or 2 stages.…”
mentioning
confidence: 99%